The effects of "Prevent Injury and Enhance Performance Program" in a female soccer team - Rodriguez, C.; Echegoyen, S.; Aoyama, T. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The purpose of this study was to evaluate the changes of muscle strength in lower limbs and knee valgus alignment using the Prevent Injury and Enhance Performance Program (PEP program) to prevent ACL injuries in female soccer players during an entire season. METHODS: A longitudinal and prospective study was done in twenty female soccer players at the Universidad Nacional Autónoma de México, from a senior team. During 24 weeks the training program was applied three times a week as a part of the team workouts. Video analysis of dynamic knee valgus alignment and maximal strength of quadriceps, hamstrings and gastrocnemius were evaluated pre and post-training. RESULTS: Quadriceps and hamstring strength increased on the right pelvic limb (P<0.001). In addition the quadriceps/hamstrings ratio decreased from 3.38 to 2.3 in the right side, and from 1.99 to 1.09 in the left side. The mechanics of jump improved in 20% of the female soccer players. Muscle strength in quadriceps and hamstrings increased in right pelvic limb (P<0.001), and the quadriceps/hamstrings ratio decreased from 3.38 to 2.3 in right side and from 1.99 to 1.09 in left side. Although injuries did not decrease during this period no ACL injury was registered. CONCLUSIONS: Until now there are no reports about muscle strength and jump technique assessment with the application of the PEP program. The neuromuscular training and muscle balance are important to prevent ACL injuries. We advise that this program is integrated to women`s soccer training.